Jesus, Why Does the Body Matter? Connecting the Passion of Christ and Peruvian Transgender Women through the Body: Connecting the Passion of Christ and Peruvian Transgender Women through the Body (KULT_online, 2024)
The theologian Elke Pahud de Mortanges analyzes the depiction of the Passion of Jesus in terms of memory, body and identity. Gaby, a transgender person and an inconstant guide in the book, leads us through the culture of memory of Christianity as well as through her own history and that of the LGBTQ community in Peru. The author opens up new multidisciplinary perspectives for Christian-oriented memory and gender studies, as well as for the concept of embodiment in the present.